Synthesis and characterization of aromatic polyazomethines bearing pendant pentadecyl chains - More, Arvind S.; Sane, Prakash S.; Patil, Anandrao S.; Wadgaonkar, Prakash P. (Polymer Degradation and Stability, 2010)
Aromatic diamine monomer viz., 4-(4'-aminophenoxy)-2-pentadecylbenzenamine containing pendant pentadecyl chain was synthesized starting from cashew nut shell liquid - a renewable resource material and was characterized by FTIR, (1)H and (13)C NMR spectroscopy. A series of new (co) polyazomethines containing pendant pentadecyl chains and flexibilizing ether linkages was synthesized by polycondensation of 4-(4'-aminophenoxy)-2-pentadecyl benzenamine with commercially available aromatic dialdehydes viz., terephthaldehyde (TPA), isophthaldehyde (IPA) and varying mixture of TPA and IPA. Inherent viscosities and number average molecular weights of (co) polyazomethines were in the range 0.50-0.70 dL/g and 10,490-40-800 (GPC, polystyrene standard), respectively indicating formation of medium to reasonably high molecular weight polymers. (Co) polyazomethines containing pendant pentadecyl chains were found to be soluble in common organic solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, m-cresol and could be cast into transparent and stretchable films from their solution in chloroform. (Co) polyazomethines were essentially amorphous in nature and the formation of loosely-developed layered structure was observed arising from the packing of pendant pentadecyl chains. Polyazomethines exhibited glass transition temperatures (T(g)) in the range 21-48 degrees C. The observed depression of glass transition temperature could be ascribed to the ``internal plasticization'' effect of pentadecyl chains. The temperature at 10% wt loss (T(10)), determined from TGA in nitrogen atmosphere of polyazomethines were in the range 434-441 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; CNSL; pentadecyl; polyazomethines; renewable; Side-chain; solubility

Synthesis and characterization of new organosoluble aromatic polyamides and polyazomethines containing pendent pentadecyl chains - Sadavarte, Nilakshi V.; Avadhani, C. V.; Wadgaonkar, Prakash P. (High Performance Polymers, 2011)
New aromatic polyamides and polyazomethines containing pendent pentadecyl chains were synthesized by polycondensation of pentadecylbenzene-1,3-diamine with (i) four commercially available aromatic diacids, viz., biphenyl-4,4'dicarboxylic acid, 4,4'-oxybisbenzoic acid, terephthalic acid and isophthalic acid, and (ii) dialdehydes, viz., terephthaldehyde, isophthaldehyde and a 50 : 50 mol% mixture of terephthaldehyde, and isophthaldehyde, respectively. Inherent viscosities of polyamides and polyazomethines were in the range 0.35-0.56 dL g(-1) and 0.33-0.38 dL g(-1), respectively, indicating the formation of medium molecular weight polymers. The presence of pendent pentadecyl chains in polyamides and polyazomethines led to an improvement in their solubility in organic solvents. Polyamides could be cast into flexible, transparent and tough films from their solution in N,N-dimethylacetamide while polyazomethines could be solution cast into transparent, flexible and stretchable films from their CHCl(3) solution. (1)H-NMR studies based on amide proton signals and azomethine proton signals indicated the presence of constitutional isomerism in the polyamides and polyazomethines. Wide-angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were amorphous in nature. X-ray diffractograms also displayed sharp reflections in the small angle region (2 theta approximate to 3 degrees) indicating the formation of layered structure arising from packing of flexible pentadecyl chains. The glass transition (T(g)) temperatures of polyamides were in the range 169-215 degrees C while T(g) values for polyazomethines were in the range 16-55 degrees C. The temperature for the 10% weight loss of polyamides and polyazomethines were in the range 430-460 degrees C and 425-440 degrees C, respectively, in a nitrogen atmosphere, which indicated their good thermal stability. Polyazomethines were also characterized by UV-Vis and photoluminescence spectroscopy and optical band gap (E(g)) values, calculated according to the maximum of the UV absorption, were found to be in the range 2.82-3.10 eV.
Keywords: High performance polymers; optical band gap; polyamides; polyazomethines; solubility